Effectiveness of personalized open-face mask combined with styrofoam fixation in radiotherapy treatment of head and neck cancers: a prospective randomized controlled trial - Fating Yang; Jingling Li; Bo Li; Lihua Zhang; Jie Li; Xiaowei Yao; Qiuxia Hu; Yutiann Yin; Changhao Liu; Lin Xu; Jian Zang; Lina Zhao; et al. (Radiation Oncology)
Abstract Objective The primary aim of this investigation is to assess the effectiveness of implementing an innovative immobilization approach, spec ically the utilization of personalized open-face masks in combination with styrofoam fixation, for head and neck cancers receiving radiotherapy. The study seeks to evaluate the influence of this method on improving patients’ precision in positioning and their overall comfort during the treatment process, in addition to exploring its potential capacity to mitigate the occurrence of anxiety and depression in this patient population. Methods A prospective, randomized controlled trial was undertaken to investigate the comparative efficacy of two immobilization approaches for the radiotherapy treatment of head and neck cancers. The experimental group was randomly assigned to receive fixation using personalized open-face masks with nose and mouth apertures, while the control group was immobilized using closed-face masks. Weekly cone-beam computed tomography (CBCT) scans were conducted pre-treatment to assess and record setup errors along three axes. Comparative analysis of setup errors and the planning target volume (PTV) margin between the two groups was performed. Furthermore, the patients’ comfort levels and anxiety and depression status were evaluated using the modified Likert questionnaire and the Hospital Anxiety and Depression Scale (HADS). Results A total of 106 patients were enrolled in the study and randomly assigned to either the experimental group (n = 53) or the control group (n = 53). There were no statistically significant differences observed between the two groups in terms of age, sex, and disease type indicating comparability. Analysis of the setup errors along different directions showed no significant differences between the experimental and control groups in the X direction (0.90 ± 0.84 mm vs. 0.92 ± 0.85 mm, p = 0.825), Y direction (1.26 ± 0.98 mm vs. 1.37 ± 1.09 mm, p = 0.172), Z direction (1.18 ± 0.84 mm vs. 1.15 ± 0.98 mm, p = 0.651), and Rtn direction (0.65 ± 0.57 vs. 0.62 ± 0.55, p = 0.489). Evaluating the local setup errors in the experimental and control groups, there were no significant differences observed in the X direction (1.13 ± 1.15 mm vs. 1.01 ± 0.89 mm, p = 0.152) and Z direction (1.31 ± 0.88 mm vs. 1.26 ± 1.17 mm, p = 0.549). However, a significant difference was found in the Y direction (1.49 ± 1.19 mm vs. 1.80 ± 1.45 mm, p = 0.003). The Rtn direction also did not show a significant difference (0.90 ± 0.81 vs. 0.84 ± 0.73, p = 0.328). The PTV margin in the X, Y, and Z directions were determined as 2.20 mm, 3.12 mm, and 2.57 mm in the experimental group and 2.35 mm, 3.58 mm, and 2.86 mm in the control group, respectively. The personalized open-face mask patients reported higher levels of comfort compared to the perforated head, neck, and shoulder thermoplastic mask (31.32 ± 1.16 vs. 30.00 ± 1.49, p < 0.001). The prevalence rates of anxiety in the experimental and control groups were as follows: (18.8% vs. 12.5%, p = 0.399), (18.8% vs. 14.6%, p = 0.584), (23.4% vs. 25%, p = 0.856), and (23.4% vs. 33.3%, p = 0.283). Conclusions In head and neck cancer radiotherapy, we propose the idea of personalized open-face mask combined with styrofoam for the first time, which can improve patient comfort without sacrificing positioning accuracy, and has a tendency to relieve patients’ tension and anxiety. It is worth promoting and using in clinical positioning.